Property rights and soil fertility management in Niger - Gavian, S. (International Livestock Centre for Africa, 1994)
This research was undertaken as a Ph.D. dissertation (Stanford University) in conjunction with the ILCA programme in Niamey, Niger. The objective of the research was similar to that of the World Bank studies: to test how land tenure affects land-improving investment, agricultural productivity and resource management. The standard hypothesis is that land tenure that is non-exclusive insecure or non-transferable will lead to under-investment and depressed factor mobility. It is further hypothesized that this will lead to inefficient agricultural production and over-exploitation of natural resources. Data were collected for the 1990–91 crop year in three villages along a rainfall gradient from 350 mm per year to 600 mm per year. A total of 60 households were interviewed in a one-visit survey. Data were collected for 134 fields farmed by those 60 households. Fields were measured and their location described, conscious manuring was recorded as a binary variable (yes/no), labour input and yields were measured from farmer recall. Bundles of millet and sorghum were added together to derive a measure of crop output. Because of the differences between owned, hawjou and borrowed land, it was possible to test two different arguments about the effects of tenure. One argument is that "security of tenure" affects the expected returns from investments. The second argument is that the transferability of land affects the mobility of factors. Land that is more transferable can be transferred to activities and uses that earn the highest returns. As measured by the average number of years farmed, rights to borrowed land are less secure than rights to hawjou or owned land. Only owned land is transferable.